Serine leucocyte proteinase inhibitor-treated monocyte inhibits human CD4+ lymphocyte proliferation - Guerrieri, Diego (2011)
Serine leucocyte proteinase inhibitor (SLPI) is the main serine proteinase inhibitor produced by epithelial cells and has been shown to be a pleiotropic molecule with anti-inflammatory and microbicidal activities. However, the role of SLPI on the adaptive immune response is not well established. Therefore, we evaluated the effect of SLPI on lymphocyte proliferation and cytokine production. Human peripheral blood mononuclear cells (PBMC) were treated with mitogens plus SLPI and proliferation was assessed by [3H]thymidine uptake. The SLPI decreased the lymphocyte proliferation induced by interleukin-2 (IL-2) or OKT3 monoclonal antibodies in a dose-dependent manner. Inhibition was not observed when depleting monocytes from the PBMC and it was restored by adding monocytes and SLPI. SLPI-treated monocyte slightly decreased MHC II and increased CD18 expression, and secreted greater amounts of IL-4, IL-6 and IL-10 in the cell culture supernatants. SLPI-treated monocyte culture supernatant inhibited the CD4+ lymphocyte proliferation but did not affect the proliferation of CD8+ cells. Moreover, IL-2 increased T-bet expression and the presence of SLPI significantly decreased it. Finally, SLPI-treated monocyte culture supernatant dramatically decreased interferon-γ but increased IL-4, IL-6 and IL-10 in the presence of IL-2-treated T cells. Our results demonstrate that SLPI target monocytes, which in turn inhibit CD4 lymphocyte proliferation and T helper type 1 cytokine secretion. Overall, these results suggest that SLPI is an alarm protein that modulates not only the innate immune response but also the adaptive immune response.